ISLAMIC UNDERSTANDING AND PRACTICES AMONG COLLEGE STUDENTS IN KALIMANTAN: IMPLICATIONS FOR DERADICALIZATION - Hasanah, Noor; Andini, Yokke (Khazanah: Jurnal Studi Islam dan Humaniora, 2024)
Radicalization in Indonesian higher education has raised significant concerns, with studies highlighting the potential vulnerability of students, particularly in science disciplines. This research examines the factors influencing radicalization among science students in Kalimantan, focusing on their understanding and practice of Islam. Data were collected through surveys and interviews at five universities in Kalimantan, including both public and Islamic institutions, with participants actively engaged in Islamic activities. The study finds that while science students exhibit curiosity about Islam, their limited access to reliable religious literature often leads them to seek information from digital content, requiring strong content-filtering skills. The research also reveals that students are interested in Islamic teachings that promote good character and enhance worship. Their views on religious diversity and tolerance have become more inclusive, though some students still hold rigid interpretations of Islam. The findings suggest that effective Islamic Education courses should align with students’ interests and contemporary issues while fostering a moderate understanding of Islam. The implications for deradicalization include designing curricula that promote critical thinking, tolerance, and national values, alongside mentorship from moderate academics to counteract extremist ideologies. This approach contributes to creating a balanced, inclusive educational environment that resists radicalization.